2009
DOI: 10.2174/138945009789753264
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Matrix Metalloproteinases in Inflammatory Conditions

Abstract: The matrix metalloproteinases (MMPs) and their endogenous regulators, the tissue inhibitors of MMPs (TIMPs) are responsible for the physiological remodelling of the extracellular matrix (ECM) in healthy connective tissues. MMPs are also involved in the regulation of cell behaviour via the release of growth factors and cytokines from the substrates they cleave, increasing the magnitude of their effects. Excess MMP activity is associated with ECM destruction in various inflammatory conditions, such as osteoarthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 0 publications
1
57
0
2
Order By: Relevance
“…38 In addition, attempts to inhibit the overproduction of MMP subtypes in OA joints by employing exogenous Timps had little clinical efficacy. 39 Interestingly, Timp2 deletion mice resulted in OA-like phenotypes. Further investigation revealed that prevention of cartilage vascularization (other than repression of MMPs) contributed to its anti-OA function.…”
Section: Discussionmentioning
confidence: 99%
“…38 In addition, attempts to inhibit the overproduction of MMP subtypes in OA joints by employing exogenous Timps had little clinical efficacy. 39 Interestingly, Timp2 deletion mice resulted in OA-like phenotypes. Further investigation revealed that prevention of cartilage vascularization (other than repression of MMPs) contributed to its anti-OA function.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the GSH skeleton is very difficult to work with due to its pharmacokinetic properties [5,10,11] , non-GSH analog inhibitors could potentially lead to an alternative approach that yields a successful drug. Furthermore, considering the potential off-target effects of metal chelation [20,21] , non-GSH analog GLOI inhibitors lacking Zn 2+ -coordination may be more suitable for lead optimization in drug development. The discoveries of indomethacin, zopolrestat and GA as GLOI inhibitors and their related complex crystal structures have demonstrated the existence of a novel non-GSH/non-Zn 2+ -chelation type of GLOI inhibitor with a carboxyl group as an essential anchor to fix the inhibitors in the active site by hydrogen bonding.…”
Section: Discussionmentioning
confidence: 99%
“…Docking and molecular dynamic simulation analyses also suggest that coordination with Zn 2+ is required for the inhibition of GLOI by curcumin, NSAIDs and flavonoids [10,18,19] . However, metal chelation is generally undesirable in drug development because of the high potential for off-target effects in the human body [20,21] . In our recent work, we determined the crystal structure of mouse glyoxalase I (mGLOI) complexed with indomethacin (inhibition constant (K i )=18 μmol/L, PDB ID: 4KYK) and zopolrestat (K i =1.2 μmol/L, PDB ID: 4KYH), revealing a novel inhibitor-GLOI binding mode [22] .…”
Section: +mentioning
confidence: 99%
“…3). The matrix metalloproteinases (MMPs) comprise a family of 24 zinc-and calcium-dependent proteases that break down proteins of the extracellular matrix and basement membrane and modulate lung remodeling, fibrosis, and inflammation (157)(158)(159)(160)(161) The MMPs regulate important aspects of the immune response and are involved in chronic diseases such as arthritis, psoriasis, chronic obstructive pulmonary diseases, and cancer (162). MMPs can be categorized by the type of tissue degraded, including collagenases (MMP1), gelatinases (MMP9), stromelysins, and elastases.…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%